2017
DOI: 10.1002/hbm.23643
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted topological organization of structural networks revealed by probabilistic diffusion tractography in Tourette syndrome children

Abstract: Tourette syndrome (TS) is a childhood-onset neurobehavioral disorder. Although previous TS studies revealed structural abnormalities in distinct cortico-basal ganglia circuits, the topological alterations of the whole-brain white matter (WM) structural networks remain poorly understood. Here, we used diffusion MRI probabilistic tractography and graph theoretical analysis to investigate the topological organization of WM networks in 44 drug-naive TS children and 41 age and gender matched healthy children. The W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 103 publications
(137 reference statements)
5
44
0
Order By: Relevance
“…In our data, we identified two nodes (left SMA and right putamen) classified as hubs in both groups. Interestingly, this was also demonstrated in a recent paper where both patients and control subjects had highly similar hub distribution ( Wen et al., 2017 ). Similarly, in adults, both the left SMA and right putamen have been shown to display increased betweenness centrality in patients ( Tinaz et al., 2015 ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In our data, we identified two nodes (left SMA and right putamen) classified as hubs in both groups. Interestingly, this was also demonstrated in a recent paper where both patients and control subjects had highly similar hub distribution ( Wen et al., 2017 ). Similarly, in adults, both the left SMA and right putamen have been shown to display increased betweenness centrality in patients ( Tinaz et al., 2015 ).…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, only one study has explored the structural integrity of the brain using WM tractography and graph theory in young patients with TS ( Wen et al., 2017 ). Also, no study has yet attempted to characterise the association between structural integrity of WM and measures of PU in patients with TS.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the underlying neurobiology of CTDs is widely noted to involve aberrant subcortical activity within the cortico-striato-thalamo-cortical motor network (Ganos et al, 2013), which EEG is not well suited to detect. However, we note that recent imaging studies and a meta-analysis of task-based neuroimaging studies failed to find significant differences in activation and network disruptions involving basal ganglia or thalamic regions (Wen et al, 2017; Wen et al, 2016). While subcortical activity likely plays a role in tic generation, there are clear cortical dysfunctions that contribute meaningfully to the CTD phenotype that are well assessed by EEG.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, aberrant visual area connectivity has been noted among individuals with CTDs. A recent study reported reduced nodal efficiencies in several occipital regions (inferior occipital gyrus and lingual gyrus) that are important for visual processing (Wen et al, 2017). DTI studies provided direct evidence for disrupted structural integrity in various WM tracts in children with CTD, including the superior and inferior fronto-occipital fasciculus (Wen et al, 2016), which are the bases for structural connectivity between the occipital and frontal regions.…”
Section: Introductionmentioning
confidence: 99%
“…Other measures, such as average path length, global efficiency, local efficiency and clustering coefficient, provide information on the integration ability or the segregation ability of the node(Stam, 2019; Achard and Bullmore, 2007; Rubinov and Sporns, 2010). Previous studies have shown disruptions in the balance between local specialization and global integration mechanisms in whole brain-structural networks (Wen et al, 2017), and defects in network maturation, reflected by losses of hub regions in resting state cortico-basal ganglia functional networks (Worbe et al, 2012) in TS.…”
Section: Introductionmentioning
confidence: 99%